Update (3.0) to LyapXool: Quadratic programming - Carlos Argáez (SoftwareX)
This is an update to PII: S2352711020303290, LyapXool is a C＋＋ program to compute complete Lyapunov functions and their orbital derivatives for any dynamical system expressed by an autonomous ordinary differential equation. New methods and improvements made in the third version are discussed. In particular, the computation of complete Lyapunov functions within quadratic programming methods are now computed by the software. These new approaches can be used to better analyse the behaviour of dynamical systems expressed as systems of autonomous equations. The structure of the program is object-oriented rather than procedural and the output formatting has been restructured to make it easier to understand. The program maintains its user friendliness. This paper describes how the code is organised, how it can be used to compute complete Lyapunov functions and their subsequent properties for dynamical systems, and it provides an interesting example of its application.